The Effect of Using the Pocket Board Media for Addition and Subtraction on Mathematics Learning Outcomes of Grade 1 Students at SDN 04 Koto Baru - Ratnawati; Asmaryadi, Ahmad Ilham; Yunadi, Rika (The Future of Education Journal, 2025)
This study aims to determine the effect of using pocket board media on the mathematics learning outcomes of Grade I students at SDN 04 Koto Baru. The background of this study is based on the low learning outcomes of students and the lack of appropriate learning media that match the characteristics of elementary school-aged children. This research uses a quantitative approach with an experimental method and a One Group Pretest-Posttest Design. The population of this study consists of all Grade I students at SDN 04 Koto Baru, totaling 22 students, all of whom were used as samples using saturated sampling techniques. The results showed that the average pretest score was 46.95, which increased to 77.90 in the posttest. The hypothesis test using a paired sample t-test resulted in a significance value of 0.000< 0.05, indicating a significant effect of using pocket board media on students’ mathematics learning outcomes. Therefore, the pocket board can be used as an effective and engaging learning medium to improve students' learning outcomes in elementary mathematics, especially in addition and subtraction material.